FATIGUE-CREEP LIFE PREDICTION FOR HIGH PRESSURE TURBINE BLADE BASED ON QAR DATA (MT) - CAO HuiLing; ZHANG Hao (Jixie qiangdu)
Based on quick access recorder（QAR）data generated by engine operation, high pressure turbine（HPT）speed ratio of the right engine N2（the ratio of actual working speed to design speed of HPT）was extracted to compile turbine blade load spectrum. A fluid-thermal-solid coupling model was established, and the thermal boundary conditions required for calculation were established by combining QAR data and thermal analysis. The temperature, stress and strain distributions of HPT blade under different working conditions were obtained by solving the fluid-thermal-solid coupling problem with finite element software. The Manson-Coffin model and Larson-Miller model were used to predict the fatigue and creep life of the blade respectively, the influence of cooling on the life of blade was mainly analyzed. Finally, the fatigue-creep life of the blade was obtained by the linear damage accumulation theory. The results show that the fatigue life of blade is improved and the creep life is significantly improved after considering internal cooling, the predicted fatigue-creep life is close to the actual life, and this method can be used to predict the remaining life of the turbine blade of the engine and make the maintenance plan.